2016
DOI: 10.1139/cjps-2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Triallate-resistant wild oat (<i>Avena fatua </i>L.): Unexpected resistance to pyroxasulfone and sulfentrazone

Abstract: Wild oat is the most economically detrimental weed species in the Canadian Prairies and effective herbicidal control options are limited due to widespread resistance to ACCase inhibitors, ALS inhibitors, and lipid biosynthesis inhibitors; therefore, evaluation of new herbicidal modes of action such as pyroxasulfone and sulfentrazone for control is critical. Two wild oat populations (HR08-210 and HR11-151) were first subjected to a discriminating dose screen to characterize resistance to ACCase and ALS inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
(33 reference statements)
1
23
0
Order By: Relevance
“…The PERTH model parametrization also reflected our experimental work documenting cross‐resistance between pyroxasulfone and prosulfocarb, and recent evidence of field populations of L. rigidum evolving resistance to the thiocarbamate herbicides such prosulfocarb and triallate and displaying a variable level of cross‐resistance to pyroxasulfone and reduced sensitivity to propyzamide . A similar pattern of cross‐resistance between pyroxasulfone and triallate has been reported in another grass weed, Avena fatua . Thus, we assumed that cross‐resistance between pyroxasulfone and prosulfocarb was the norm in our modelled species L. rigidum despite exceptions to the norm in a variable species such as L. rigidum often being expected .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The PERTH model parametrization also reflected our experimental work documenting cross‐resistance between pyroxasulfone and prosulfocarb, and recent evidence of field populations of L. rigidum evolving resistance to the thiocarbamate herbicides such prosulfocarb and triallate and displaying a variable level of cross‐resistance to pyroxasulfone and reduced sensitivity to propyzamide . A similar pattern of cross‐resistance between pyroxasulfone and triallate has been reported in another grass weed, Avena fatua . Thus, we assumed that cross‐resistance between pyroxasulfone and prosulfocarb was the norm in our modelled species L. rigidum despite exceptions to the norm in a variable species such as L. rigidum often being expected .…”
Section: Discussionsupporting
confidence: 52%
“…Resistance to trifluralin has evolved in L. rigidum after several years (>10 years) of widespread use and high selection pressures, but it remains at relatively low levels in Australia . Field resistance to pyroxasulfone has been recently reported in Avena fatua from Canada . In L. rigidum , resistance to pyroxasulfone has been selected after only three generations of recurrent low‐dose selection in glasshouse studies, but the empirical evidence indicates it is rare in L. rigidum ‐unselected populations in the field with values possibly lower than 10 −7 .…”
Section: Methodsmentioning
confidence: 99%
“…A population of Avena fatua recently was reported resistant to the PPO inhibitor sulfentrazone applied PRE, despite not having been previously exposed to this herbicide. 36 The authors suggested that sulfentrazone resistance could be conferred by increased endogenous gibberellin content (allowing for more rapid germination and emergence), or enhanced cytochrome P450 activity, both of which were selected by exposure to other herbicides (triallate and acetolactate synthase (ALS) and acetyl-CoA carboxylase (ACCase) inhibitors, respectively). A second example involves an A. tuberculatus population initially identified as being resistant to p-hydroxyphenylpyruvate dioxygenase (HPPD)-inhibiting herbicides.…”
Section: Use Of Ppo Herbicidesmentioning
confidence: 99%
“…There are at least a couple of cases in which resistance to PPO inhibitors probably occurred as a result of selection by herbicides with different target sites. A population of Avena fatua recently was reported resistant to the PPO inhibitor sulfentrazone applied PRE, despite not having been previously exposed to this herbicide . The authors suggested that sulfentrazone resistance could be conferred by increased endogenous gibberellin content (allowing for more rapid germination and emergence), or enhanced cytochrome P450 activity, both of which were selected by exposure to other herbicides (triallate and acetolactate synthase (ALS) and acetyl‐CoA carboxylase (ACCase) inhibitors, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…The relatively new herbicide pyroxasulfone (VLCFA inhibitor) has become widely used in Australia, U.S.A and Canada. In Canada a recent study reported field-evolved resistance to pyroxasulfone and triallate in A. fatua (Mangin et al, 2016). No field-evolved pyroxasulfone-resistant L. rigidum populations have thus far been identified, however we experimentally evolved pyroxasulfone resistance in L. rigidum by recurrent low-dose pyroxasulfone selection over a few generations (Busi et al, 2012) and showed cross-resistance to the thiocarbamates prosulfocarb and triallate rapidly evolving in field collected populations (Busi and Powles, 2013, 2016).…”
Section: Introductionmentioning
confidence: 99%